Serotyping of Intestinal Bacilli Causing Diarrhea Isolated from Children and Detection of their Antibiotics Resistance - R Yousefi Mashouf; AA Moshtaghi (Tehran University of Medical Sciences, 2007)
Background: Bacterial diarrhea is very common in particular in devoloping countries and is still one of the most causes of mortalities in children.The aim of present study was to identify the most common of bacterial agents causing acute bacterial diarrhea in children under 12 years old and detection of their resistance to antibiotics in patients who referred to pediatrics department of university hospitals of Hamadan. Methods: During two years) 2003-2005(, 610 samples obtained from children under 12 years old with gastroentrotitis were investigated for bacterial cultures, frequency of age, serotyping of isolates and antibiogram patterns. Polyvalent (I, II, III, IV) and monovalant antisera (055, 0111, 011, 086, 026, 0125, 0119, 0146, 0128, 0142, 0157) were used for serotyping of E. coli (EPEC). Antibiogram tests were also performed by gel-diffusion method of Kirby-Bauer. The data were gathered through a questionnaire and analysed using spss software. Results: Out of 610 tested samples, 155 cases (25.4%) had positve culture for intestinal pathogenic bacilli. The most common isolate was; Escherichia coli (EPEC) with 105 cases (67.8%) and the lowest isolate was Shigella with 18 cases (11.6%). The most common serotype of E. coli was 0128 (26.6%) and the lowest serotype was 0119 (5.7%). The most common serotypes of Salmonella were S.typhi (34.4%) and S.typhimurium and the lowest serotype was S. para A (3.1%). The most common serotype of Shigella was S.sonnei (55.6%) and the lowest serotype was S. boydii (5.6%). The most effective antibiotics against bacteria were ceftriaoxne, nitrofurantoin, imipenem, amikacin and gentamycin, but they showed high resisitance to ampicillin, cephalexin, trimethoprim and chloramphenicol. Conclusion: The present study showed that gram negative bacilli in particular, Escherichia coli (EPEC) and Salmonella species are predominant causes of bacterial diarrhea in children under 12 years old in this region. In many other countries, the most common serotypes of E. coli are 0157 and 055, but in our study the serotype of 0128 was common. Most species showed high resisitance to routine antibiotics such as ampicillin, trimethoprim and chloramphenicol.